Pengaruh Kualitas Jasa Bank Syariah terhadap Kepuasan Nasabah pada Bank Muamalat Indonesia Cabang Semarang - - Hasan (Universitas Wahid Hasyim, 2006)
Customer satisfaction could different on different of time, place and customer. Satisfaction on service institution is almost linked with service quality. The research explored effect syariate bank service quality on customer satisfaction in Semarang Branch of Bank Muamalat Indonesia. Service quality on this research referred on six dimentions of banking service quality which had been stated by Othman and Owen (2001), included of compliance, assurance, reliability, tangibles, empathy, and responsiveness (CARTER). Compliance dimention was the uniqueness dimention on syariate service institution, specially on syariate bank. Based on 100 (one hundred) Semarang branch customer respondents of Bank Muamalat Indonesia was yield three significant dimentions e.g.: responsiveness, assurance, and compliance, while the four others did not significant. But the CARTER model was still good to predict customer satisfaction, referred on determinant coeffitien and F test product. Based on classical assumption test product the regression model could be categorized as good